Analisis Studi Literatur Meningkatkan Kemampuan Pemecahan Masalah Computational Thinking Pada Siswa Madrasah Ibtidaiyah - Desmi Fitri Syahdani Br Sitepu; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This literature study analysis discusses improving computational thinking problem solving abilities in madrasah ibtidaiyah students. In this study, an analysis of various literature that has been carried out previously was carried out to understand how the use of computational thinking can improve problem solving abilities in madrasah ibtidaiyah students. One of the journals that is relevant to this topic is